Meiji Restoration and Modernization: The Role of Intellectuals in The Context of Gramsci’s Theory of Hegemony and Counter-Hegemony - Yazici, Yasemin (European Scientific Journal, ESJ, 2025)
The Meiji Era (1868-1912) was a crucial period in Japan’s modernization, marked by profound social and political transformations under Western influence. Japanese intellectuals played a key role in reconciling traditional values with modern Western ideas. Inspired by Western science, technology, and administrative systems, the Meiji government sought to reshape Japan into a global power. Intellectuals explored concepts such as freedom, democracy, and individualism, integrating them into Japanese society while maintaining cultural identity. This study examines the impact of Meiji intellectual movements on Japan’s modernization. The central questions include: How did Japanese intellectuals interpret Western thought? What proposals did they offer for modernization? How did their views on "civilization" and "enlightenment" influence state policies? What tensions arose between traditional values and Western modernization ideas? Addressing these questions, this study explores the intellectual foundation of Japan’s transformation into a modern nation-state. Additionally, using Gramsci’s hegemony theory and ideology analysis, it investigates how the ruling class employed ideological tools to shape modernization. Findings reveal that Meiji intellectuals sought a balance between tradition and modernization. They aimed to preserve Japan’s national identity while embracing scientific and technological advancements. This dual approach aligned with Gramsci’s theory of hegemony, which stresses obtaining societal consent for change. Ultimately, the Meiji intellectual movements shaped Japan’s policies, fostering a unique modernization process that blended Western influences with indigenous traditions. This dynamic balance allowed Japan to emerge as a strong, modernized state while maintaining its cultural heritage.